Application of Abraham's solvation parameter model to extractables and leachables studies in pharmaceutical and medical device industries: A tutorial - Jianwei Li (Journal of Chromatography Open)
The Abraham's solvation parameter model is an important tool to model and predict distribution properties of compounds in numerous partitioning systems in chemistry, environmental chemistry, medicine, and biology. The evaluation of the distribution properties in extractables and leachables (E&L) studies in pharmaceutical and medical device industries is another major application of this model. This tutorial is aimed at illustrating the applications of the model in E&L studies. Specific examples of the application illustrated in this tutorial include: (a) establishment of equivalent or similar solvents; (b) determination of polarity of solvents, biological tissues, and materials; (c) development of drug product simulating solvents; (d) understanding solvent extraction power for a material; (e) selection of solvent and standards in pretreatment of extraction samples; and (f) chromatography retention prediction for E&L.